Marketing management strategies for msmes: Examining the role of service quality, product quality, and price in shaping brand image - Agustin, Anisa (Journal of Economic, Business & Accounting Research, 2025)
Background: The success of a company is closely related to effective marketing management. One of the key elements in marketing is brand image, which is shaped by service quality, product quality, and price. This study aims to determine the influence of service quality, product quality, and price on brand image, both partially and simultaneously. Methods: This research employs a quantitative approach using primary data collected through questionnaires. The sampling technique used is non-probability sampling with a purposive sampling approach. A total of 100 respondents were selected based on Cochran's formula, due to the unknown size of the population. The data were analyzed using multiple linear regression. Findings: The results of this research indicate that there is a positive and significant influence of service quality on the brand image, there is a positive and significant influence of product quality on the brand image, there is a positive and significant influence of price on the brand image, there is a positive and significant influence of service quality, product quality, and price on the brand image. Conclusion: In conclusion, service quality, product quality, and price have a positive and significant effect on brand image, both individually and simultaneously. These findings offer important implications for the development of marketing strategies, particularly for small and medium enterprises (SMEs). Novelty/Originality of this article: The novelty of this research lies in the simultaneous analysis of the three variables' influence on brand image within the context of a local home industry. The focus on SMEs using a quantitative approach makes this study both unique and relevant for designing effective marketing strategies for small business actors.